NFC Data Security Using Hill Cipher - Hutagalung, Gabriel Ardi; Dalimunte, Yulia Agustina; Khairina, Isni; Lubis, Muthi'ah Zahra; Firmansyah, Darma; Sinaga, Desi Natalia; Simanjuntak, Indah Sari; Indandi, Zanuar (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Near Field Communication (NFC) technology has become ubiquitous in various applications, from contactless payments to data transfer between devices. As the use of NFC expands, ensuring the security of transmitted data becomes paramount. This research investigates the application of Hill Cipher, a linear algebra-based encryption technique, to enhance the security of data transmitted via NFC. In the field of contemporary wireless technology, near-field communication (NFC) stands out as an important force, enabling contactless transactions and the seamless exchange of information between electronic devices. This research explores the innovative integration of NFC into the attendance input process, which is linked to a website-based attendance system. NFC's adaptability, which was initially prominent in payment cards, has expanded across industries, empowering smartphones, tablets, and wearable devices. This study contributes to the ongoing development of NFC technology, proposing a renewable solution for student attendance systems. With a vision of increased efficiency, this research anticipates increased utilization of time and resources, thereby providing a promising path for the advancement of attendance management. A comprehensive evaluation of the proposed NFC data security solution was conducted through simulations and practical implementations. The research assesses the impact on communication speed, energy consumption, and overall system performance. Results indicate that the integration of Hill Cipher introduces a negligible overhead on communication speed, making it a viable option for real-time NFC applications. Furthermore, the study addresses potential vulnerabilities and threats associated with NFC technology, emphasizing the role of Hill Cipher in mitigating risks such as eavesdropping and unauthorized data interception. The research considers practical implementation challenges and proposes strategies for seamless integration into existing NFC-enabled devices. In conclusion, this research contributes to the ongoing discourse on NFC data security by introducing Hill Cipher as a robust encryption mechanism. The findings underscore the feasibility of implementing this encryption technique without compromising the efficiency of NFC communication. The proposed secure communication protocol holds promise for enhancing the privacy and integrity of data transmitted via NFC, fostering trust in the expanding ecosystem of NFC-enabled applications.